Center of mass and center of buoyancy in physically impaired swimmers - Hohrai, T.; Tachi, M.; Ohnuma, H.; Wakayoshi, K. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
The purpose of this study was to investigate the longitudinal and transverse axes position of center-of-mass (LCM, TCM) and center-of-buoyancy (LCB, TCB) in physically impaired swimmers. Ten physically impaired elite swimmers participated in this study. The participants lay prone and took a streamlined posture on a customized platform which was held with three tension sensors. During center-of-mass measurement, the participants and the platform were held above the water. Subsequently, center-of-buoyancy was measured, while the participant`s body and the platform were totally submerged under the water. The participants maintained the same posture during center-of-mass and center-of-buoyancy measurements. During the measurement of center-of-buoyancy, the participants used a snorkel and continued breathing. The measurement was carried out for one minute. Center-of-mass and center-of-buoyancy were calculated using the values from the tension sensors. Because center-of-mass and center-of-buoyancy changes with breathing, the data for a period of three ventilation cycles was averaged and analyzed. In nine out of ten participants, LCB was located superior to LCM. This result was similar to that reported for non-disabled swimmers in other studies. However, the distance between LCB and LCM was closer in the lower limb amputee participants than in the upper limb amputee participants. In paralyzed participants, the distance between LCB and LCM did not seem to correlate with the part of paralysis. The body part of amputation or paralysis did not show a consistent effect on TCM and TCB.